Morphology effects of CeO2 for catalytic oxidation of formaldehyde. Issue 3 (June 2022) - Chang, Tingting; Wang, Zhimiao; An, Hualiang; Li, Fang; Xue, Wei; Wang, Yanji
Abstract: Formaldehyde (HCHO) is a primary indoor air pollutant, and can cause serious environmental and health problems. In this study, CeO2 spherical-like aggregate of nanoplates (CeO2 -S) were prepared for the HCHO oxidation, and the efficiency of CeO2 -S was compared with those of CeO2 nanorods and nanocubes. CeO2 -S showed excellent activity, with a maximum HCHO conversion of 87% at 120 °C using a gas hourly space velocity of 10 000 mL·gcat −1 ·h −1 and HCHO concentration of approximately 500 ppm. The catalysts were characterized using thermal and spectroscopic techniques, revealing that the excellent catalytic performance of CeO2 -S originated in its abundant surface hydroxyl and oxygen groups. In situ FT-IR results indicated that dioxymethylene and formates were the main intermediates in HCHO oxidation. Further oxidation of formates produced CO2 and H2 O, and CO2 reacted with surface hydroxy groups to form carbonate species, which accumulated on the catalyst surface, thus deactivating the CeO2 catalysts and inhibiting complete conversion of HCHO. Graphical Abstract: ga1 Highlights: Preparation of CeO2 with different morphologies. CeO2 spherical-like aggregate of nanoplates show higher activity than that of CeO2 nanorods and nanocubes. CeO2 spherical-like aggregate of nanoplates have abundant surface hydroxyl group and surface oxygen species. The mechanism of HCHO oxidation over CeO2 is proposed.